APLIKASI MEDIA PEMBELAJARAN KISAH NABI DAN RASUL BERGELAR ULUL AZMI BERBASIS ANDROID (STUDI KASUS : MI TANWIRIYYAH) - Dayanni Vera Versanika; Rahmat Jaenal; Azka Siti Mukaziyah (Jurnal Teknologi Informasi dan Komunikasi, 2024)
The emergence of the covid-19 pandemic forced parents to give gadgets to students. With the gadget in their midst, children spend more time playing gadgets. Of course the emergence of this gadget brings various positive and negative impacts. The negative impacts that arise include lazy learning and unstable student emotions. That way the student becomes irritable. with this case the author finally designed the Learning Media Application For The Story Of Babi and The Apostle With The Title Ulul Azmi Based On Android. The existence of this application in addition to being able to minimize the negative impact on the use of gadgets on students this application also helps teachers in conveying ulul azmi material as a learning companion tool. The teaching and learning process becomes more interesting for students and students become more active when the teacher is delivering the material.